2012
DOI: 10.4161/rna.9.1.18277
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogenes are not pseudo any more

Abstract: Recent significant progress toward understanding the function of pseudogenes in protozoa (Trypanosoma brucei), metazoa (mouse) and plants, make it pertinent to provide a brief overview on what has been learned about this fascinating subject. We discuss the regulatory mechanisms of pseudogenes at the post-transcriptional level and advance new ideas toward understanding the evolution of these, sometimes called "garbage genes" or "junk DNA," seeking to stimulate the interest of scientists and additional research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…We have demonstrated that pseudogenes play important regulatory functions in T. brucei (Wen et al 2011(Wen et al , 2012. In the present study, we have further demonstrated that pseudogenes could form a complex regulatory network with other transcripts in the NAT manner and could generate siRNAs, although this phenomenon was not observed by Tschudi and colleagues (Tschudi et al 2012), who have suggested that the majority of pseudogenes do not generate small RNAs in the procyclic form of T. brucei.…”
Section: Sf Pfmentioning
confidence: 38%
“…We have demonstrated that pseudogenes play important regulatory functions in T. brucei (Wen et al 2011(Wen et al , 2012. In the present study, we have further demonstrated that pseudogenes could form a complex regulatory network with other transcripts in the NAT manner and could generate siRNAs, although this phenomenon was not observed by Tschudi and colleagues (Tschudi et al 2012), who have suggested that the majority of pseudogenes do not generate small RNAs in the procyclic form of T. brucei.…”
Section: Sf Pfmentioning
confidence: 38%
“…Several lines of evidence have recently challenged the view that all DOA elements should evolve neutrally [9,13]. In this regard, an indication of the action of natural selection on a sequence can be obtained by studying the ratio of synonymous to non-synonymous substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…Although all of the pseudogenes used in this study appeared to be disabled, their sequence evolutionary rates were analysed, as several studies have demonstrated that pseudogenes can undergo exaptation for other functions [9,13]. As most amino-acid changes (i.e., non-synonymous substitutions) are selected against in coding sequences, functional genes are expected to have significantly lower Ka/Ks ratio than pseudogenes.…”
Section: Pseudogene Evolutionary Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, transcribed pseudogenes, including those that arose via retroposition, reportedly can be functional as RNAs or mRNAs encoding truncated proteins (Balakirev and Ayala 2003;Duret et al 2006;Frith et al 2006b;Pink et al 2011;Wen et al 2012;Sen and Ghosh 2013). For example, retropseudogene PTENP1 derived from tumor suppressor gene PTEN is transcribed.…”
Section: Competitive Rnasmentioning
confidence: 99%